2014
DOI: 10.4236/jbbs.2014.410046
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effect of <i>Citrus aurantium</i> L. Essential Oil on Anxiety and Its Interaction with GABAergic Pathways in Male Mice

Abstract: Anxiety is among the most common disorders affecting a great number of people. Different neurotransmitter systems, such as GABAergic system, play an important role in emergence of anxietyrelated behaviors. In this study, we have investigated the effect of Citrus aurantium L. essential oil on anxiety and its interaction with GABAergic pathways. Male mice were assigned into control, sham, and experimental groups. Intraperitoneal injection of Citrus aurantium L. essential oil was applied at doses of 0.5, 2.5, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The same group evaluated the co-administration effects of C. aurantium L. with diazepam [29]. They found that C. aurantium L. essential oil (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…The same group evaluated the co-administration effects of C. aurantium L. with diazepam [29]. They found that C. aurantium L. essential oil (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…Although diazepam increased open arms exploration (percentage of time spent and percentage of entries), coadministration with Citrus aurantium reduced the anxiolytic effect of diazepam. Flumazenil did not alter the effect of Citrus aurantium ; however, authors suggest that Citrus aurantium L. may exert an anxiolytic-like effect acting as partial agonist at the GABA-A receptor/benzodiazepine site [52]. Preclinical antianxiety effects of Citrus aurantium are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…During the experiment it was observed that the animals submitted to the elevated cross test, both those treated with the control drug and those treated with the essential oil, showed a significant increase in the length of stay in the open arms. When the essential oil was applied simultaneously with diazepam, the results were even more significant, indicating a reduction in anxiety (Khosravi et al, 2014). Furthermore, additional studies have shown that essential oil can decrease or increase the responsiveness of nociceptors.…”
Section: Activity Of Neroli Essential Oil On the Cnsmentioning
confidence: 96%